2023
DOI: 10.33321/cdi.2023.47.1
|View full text |Cite
|
Sign up to set email alerts
|

The epidemiology of the COVID-19 pandemic in the small, low-resource country of Timor-Leste, January 2020 – June 2022

Abstract: Timor-Leste, a small, mountainous half-island nation which shares a land border with Indonesia and which is 550 km from Australia, has a population of 1.3 million and achieved independence for the second time in 2002. It is one of the poorest nations in Asia. In response to the global coronavirus disease 2019 (COVID-19) pandemic, the Timor-Leste Ministry of Health undertook surveillance and contact tracing activities on all notified COVID-19 cases. Between 1 January 2020 and 30 June 2022, there were 22,957 cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(25 citation statements)
references
References 0 publications
2
23
0
Order By: Relevance
“…[26] The situation was worsening during 2021 due to community transmission of Delta and Omicron variant in the country caused many deaths and hospitalization. [21]This finding of maternal and child health services disruption was similar with research findings from many developing countries in Asia and Africa region. [3] [10] [11] [12] [13].…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…[26] The situation was worsening during 2021 due to community transmission of Delta and Omicron variant in the country caused many deaths and hospitalization. [21]This finding of maternal and child health services disruption was similar with research findings from many developing countries in Asia and Africa region. [3] [10] [11] [12] [13].…”
Section: Discussionsupporting
confidence: 85%
“…The interruption of services delivery in Timor-Leste may be caused by many reasons including lockdown restriction and mandatory stay home order implemented in the country from April 2020 to November 2021. [20] [21] Interviews with healthcare providers and clients from study in Ethiopia highlighted several barriers to service utilization during COVID-19, including fear of disease transmission, economic hardship, and transport service disruptions and restrictions. [11] Kapoor and collaegues.2022, in their study found a causal link between restrictions and health service utilization and call for policy makers in low- and middle-income countries to carefully consider the trade-offs of strict lockdowns during future COVID-19 waves or future pandemics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations